2022
DOI: 10.1128/aem.02517-21
|View full text |Cite
|
Sign up to set email alerts
|

Litter Commensal Bacteria Can Limit the Horizontal Gene Transfer of Antimicrobial Resistance to Salmonella in Chickens

Abstract: Antimicrobial resistance spread is a worldwide health challenge, stemming in large part from the ability of microorganisms to share their genetic material through horizontal gene transfer. To address this issue, many countries and international organizations have adopted a One Health approach to curtail the proliferation of antimicrobial-resistant bacteria.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Fluoroquinolones resistant was mediated by efflux pumps that reduce the permeability of the antibiotic (Yedekci et al, 2012). The results of the current study confirmed that a high percentage of MDR and XDR K. pneumoniae was detected which may due to the ability of bacterial cells to acquisition of resistance genes that transmitted horizontally or vertically where the horizontal transfer of genes is the most effective and dangerous, as it works on spreading genes easily between different strains, either through plasmids or transposons (Oladeinde et al, 2022).…”
Section: Resultssupporting
confidence: 73%
“…Fluoroquinolones resistant was mediated by efflux pumps that reduce the permeability of the antibiotic (Yedekci et al, 2012). The results of the current study confirmed that a high percentage of MDR and XDR K. pneumoniae was detected which may due to the ability of bacterial cells to acquisition of resistance genes that transmitted horizontally or vertically where the horizontal transfer of genes is the most effective and dangerous, as it works on spreading genes easily between different strains, either through plasmids or transposons (Oladeinde et al, 2022).…”
Section: Resultssupporting
confidence: 73%
“…Jurburg et al (2019) also reported that Escherichia/Shigella and Streptococcus were the major taxa found in fecal samples of one-day old broiler chicks. Similarly; Cárdenas-Rey et al (2022), showed that Escherichia/Shigella was in high abundance in the ceca of one-day old broiler chicks (relative abundance of 37.3% ± 24.0%). Together, these results suggest that the bacterial taxa found in the meconium of day-one old chicks in the study were under selection in the hatchery.…”
Section: Discussionmentioning
confidence: 81%
“…Early studies on the competitive exclusion properties of reused litter have shown a lower survival of Salmonella in reused litter compared to fresh litter ( Tucker, 1967 ; Fanelli et al, 1970 ; Gustafson and Kobland, 1984 ; Soerjadi-Liem and Cumming, 1984 ; Corrier et al, 1992 ). Recent studies have shown that chickens raised on reused litter harbor a different microbiome than chicks grown on fresh litter ( Cressman et al, 2010 ; Wang et al, 2016 ; Oladeinde et al, 2022 ) and that the number of litter samples positive for Salmonella significantly decreases as the number of litter reuses increased compared with the first use of the litter ( Roll et al, 2011 ; Chinivasagam et al, 2012 ; Muniz et al, 2014 ; Oladeinde et al, 2022 ). Roberts et al (2013) detected Salmonella at a greater frequency with the first flock of broilers raised on fresh pine shavings compared to flock 2 and 3.…”
Section: Discussionmentioning
confidence: 99%